(untitled) (Al-Qamar, 2022)
Imam Badr al-Din al-Aini is considered one of the iconic commentators of Sahih al Bukhari, the most prestigious treatise of Hadith literature. He hailed from Turkey leaving a rich life and legacy dedicated to the service of Prophetic tradition compounded in his acclaimed work “Umadat-ul-Qaari” .This article aims at expounding the preferences established by Imam al-Aini between varied opinions of Qur’anic Interpartaion. He considered the verses mentioned by Imam al-Bukhari as reference keys and developed further insights. While doing so he primarily relied on classical Interpartaion literature especially the magnum opus of al-Tabari, Jam’I-ul-Bayan. Al-Aini established that the principal maxims of establishing preferences in varied Tafseer opinions are multifold and multi dimensional and that consolidated conclusions can only be drawn after their thorough investigation and insightful reading. Al-Aini used multiple new connotations while establishing his own preferences as wll as he relied on already affirmed variables of al Samarqandi, Ibn-e-Kathir and al-Thalabi. He also marked some notable preferences pertaining to varied readings of Qur’anic text (al-Qira’aat) and various grammatical insights.